2002
DOI: 10.1055/s-2002-38246
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Adiponectin Protein Expression: Effect of Fat Depots and Type 2 Diabetic Status

Abstract: Adiponectin is an adipocyte-derived hormone associated with insulin sensitivity and atherosclerotic risk. As central rather than gluteofemoral fat is known to increase the risk of type 2 diabetes and cardiovascular disease, we investigated the mRNA and protein expression of adiponectin in human adipose tissue depots. RNA was extracted from 46 human adipose tissue samples from non-diabetic subjects aged 44.33 +/- 12.4 with a BMI of 28.3 +/- 6.0 (mean +/- SD). The samples were as follows: 21 abdominal subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
2
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 21 publications
8
77
2
4
Order By: Relevance
“…10,11 However, the data in type 2 diabetic patients are conflicting. 19,34,39,40 Our results, while confirming lower expression and plasma concentrations in association with obesity, do not show an independent effect of hyperglycemia, in agreement with Koistinen et al 40 On the other hand, our diabetic subjects were all severely obese, so that expression and circulating levels may have bottomed out (a 'floor effect'). Therefore, we cannot completely rule out that hyperglycemia in non-obese (or less obese) subjects may be associated with suppressed ApN.…”
Section: Discussionsupporting
confidence: 90%
“…10,11 However, the data in type 2 diabetic patients are conflicting. 19,34,39,40 Our results, while confirming lower expression and plasma concentrations in association with obesity, do not show an independent effect of hyperglycemia, in agreement with Koistinen et al 40 On the other hand, our diabetic subjects were all severely obese, so that expression and circulating levels may have bottomed out (a 'floor effect'). Therefore, we cannot completely rule out that hyperglycemia in non-obese (or less obese) subjects may be associated with suppressed ApN.…”
Section: Discussionsupporting
confidence: 90%
“…23 Similar to the reported differences in adiponectin expression 17,18 and estradiol formation, 14,16 insulin responsiveness also appears to be different between subcutaneous and visceral adipocytes of nondiabetic obese subjects; the latter showing decreased responsiveness attributable to reduced insulin receptor autophosphorylation and reduced expression and tyrosine phosphorylation of insulin receptor substrate 1 (IRS-1). 24 Prolonged exposure of adipocytes to increased plasma estradiol, for example, during pregnancy 25 or in women with central obesity, 26,27 appears to be to prone to decreased IRS-1 expression.…”
Section: Discussionmentioning
confidence: 56%
“…In further support, subcutaneous adipocytes (both abdominal and gluteal) of nondiabetic obese subjects were shown to have maintained high adiponectin expression/secretion compared with the low expression/secretion of visceral adipocytes. 17,18 In diabetic subjects, adiponectin expression/secretion of subcutaneous adipocytes is also low, 18 suggesting that hormonal milieu characteristics for insulin-resistant/centrally obese subjects may inhibit adiponectin in both fat depots. Hormonal changes characteristic for centrally obese women versus generally and peripherally obese women included markedly decreased SHBG and increased estradiol levels.…”
Section: Discussionmentioning
confidence: 99%
“…16,93 There is a negative association between adiponectin and waist-to-hip ratio, central fat mass accumulation and visceral fat mass. 6,88,[94][95][96][97] Further, in vitro studies have shown that adiponectin protein content and mRNA expression are lower in visceral adipocytes 98 and that with increasing visceral fat mass adiponectin secretion from those cells is decreased, whereas secretion rates from subcutaneous adipocytes remain unaffected. 99 There is also a differential expression pattern of adiponectin receptor 1 with high levels of expression in subcutaneous fat.…”
Section: Adiponectinmentioning
confidence: 99%